PENGARUH KUALITAS PRODUK DAN PERSONAL SELLING TERHADAP KEPUASAN PELANGGAN PADA MAJALAH INFO BEKASI (STUDI KASUS PT. SIBK) - Rizan, Mohammad; Anjarestu, Yogha (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2013)
Generally, the purpose of this research are: 1) To know the description of product quality, personal selling and customer satisfaction on client of Info Bekasi Magazine. 2) To know the influence of quality product towards customer satisfaction on client of Info Bekasi Magazine. 3) To know the influence of quality product towards customer satisfaction on client of Info Bekasi Magazine. 4) To know the influence of quality product and personal selling simultaneously towards customer satisfaction on client Info Bekasi Magazine. The method implemented in this research are descriptive explanatory and causal. This research is taken 100 client of Info Bekasi Magazine after their interact with personal selling used field pricing system while data was collected by using questionnaire and processed using SPSS 20. The result shows that partially quality product has a positive and significant impact toward customer satisfaction. Then, partially personal selling also has a positive and significant impact toward customer satisfaction. Simultaneously, quality product and personal selling have a positive and significant impact toward customer satisfaction. The empirical findings indicate that to create and improve the customer satisfaction, Info Bekasi Magazine need to consider quality product and personal selling because those factors shown to affect the level of job loyalty. Keywords: Quality Product, Personal Sellling, Customer Satisfaction